Ferromagnetism induced by hydrogen in polycrystalline nonmagnetic Zn0.95Co0.05O - Deka, Sasanka; Joy, Pattayil Alias (Applied Physics Letters, 2006)
Polycrystalline Zn0.95Co0.05O is found to be paramagnetic at room temperature and down to 12 K. Optical measurements prove the incorporation of Co2+ ions inside the ZnO lattice in the tetrahedral site. When the paramagnetic sample is heated in Ar/H-2 at 1125 K for 2 h, ferromagnetism with a very high value of magnetization is observed at room temperature. Hydrogen reduction does not affect the substituted Co2+ ions inside the wurtzite crystal lattice as evidenced from optical studies. X-ray diffraction studies show the presence of Co metal after the reduction process which is the origin of room temperature ferromagnetism. (c) 2006 American Institute of Physics.